2022
DOI: 10.1136/bmjspcare-2021-003240
|View full text |Cite
|
Sign up to set email alerts
|

Patient–caregiver dyads advance care plan value discussions: randomised controlled cancer trial of video decision support tool

Abstract: ObjectiveUptake of advance care planning (ACP) in cancer remains low. An emphasis on personal value discussions and adoption of novel interventions may serve as the catalyst to increase engagement. This study examined the effectiveness of a video decision support tool (VDST) modelling values conversations in cancer ACP.MethodsThis single site, open-label, randomised controlled trial allocated patient–caregiver dyads on a 1:1 ratio to VDST or usual care (UC). Previously used written vignettes were converted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Interventions in this category involved the use of a question prompt list (QPL; one RCT) [12] and videos (two RCTs) [13][14][15][16]. The QPL was adapted from a booklet used in America and Australia [43], to promote discussions about prognoses and EoL issues with patients with advanced cancer and estimated life expectancies less than 1 year attending outpatient palliative care consultations [12].…”
Section: Intervention Tools For Patients and Caregiversmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions in this category involved the use of a question prompt list (QPL; one RCT) [12] and videos (two RCTs) [13][14][15][16]. The QPL was adapted from a booklet used in America and Australia [43], to promote discussions about prognoses and EoL issues with patients with advanced cancer and estimated life expectancies less than 1 year attending outpatient palliative care consultations [12].…”
Section: Intervention Tools For Patients and Caregiversmentioning
confidence: 99%
“…In another RCT, the effectiveness of a video decision support tool (VDST) based on video vignettes designed to facilitate value-based ACP discussions across three cancer trajectory stages among patients with cancer and their designated caregivers was examined [ 14 ]. Relative to usual care (receipt of the hospital's ACP document and verbal and written guidelines) [ 14 ], the intervention had no impact on ACP document completion overall, but it enhanced such completion in older (aged ≥70 years) relative to younger (aged <70 years) patients [ 15 ]. Qualitative analyses of the contents of patients’ ACP value directives revealed that the choices people make as they approach death relate to their most deeply held values, highlighting the usefulness of discussing value directives during ACP [ 16 ].…”
Section: Main Randomized Controlled Trial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation